Dynamics of Meaning-Making among Adult Survivors of Online Child Sexual Exploitation and Abuse (OCSEA) - Charles Prawira Chayadi; Nanda Audia Vrisaba (International Journal of Science and Environment (IJSE), 2026)
Online Child Sexual Exploitation and Abuse (OCSEA) is a form of technology-facilitated sexual violence that may have enduring psychological consequences extending into adulthood. Although previous studies have documented its adverse impacts, limited research has examined how adult survivors construct meaning from these experiences. This study aimed to explore the factors influencing the meaning-making process, understand the dynamics of meaning making, and identify the meanings reconstructed by adult survivors of OCSEA. This study employed a qualitative research design using Interpretative Phenomenological Analysis (IPA). Participant screening was conducted using the Global Psychotrauma Screen (GPS) to identify adult survivors who had experienced OCSEA during childhood or adolescence and demonstrated sufficient psychological functioning to reflect on their experiences. Three adult female survivors participated in semi-structured interviews. Data were analyzed using IPA and interpreted through Park’s Meaning Making Model. The findings indicate that meaning making is a complex, dynamic, and non-linear process influenced by both internal and external factors. Internal factors included emotional needs, self-reflection, and future aspirations, whereas external factors comprised healthy interpersonal relationships, psychoeducation, and exposure to information regarding sexual violence. Participants experienced disruptions in their global meaning concerning themselves, interpersonal relationships, and the digital world, which motivated cognitive and emotional meaning-making processes. These processes resulted in adaptive meaning made, including identity reconstruction, greater independence, increased interpersonal and digital vigilance, and the development of new life purposes, such as educating others, supporting family members, and helping individuals with similar experiences. These findings highlight the diverse pathways through which adult survivors integrate traumatic experiences into meaningful life narratives.